Is the vertebral canal prepared to host the aged spinal cord? : A morphometric assessment - Nishida, Fabián (2014)
Although the interaction between the growing spinal cord and the vertebrae has been widely demonstrated for mammal’s prenatal and early postnatal life, there is no extensive knowledge about this interaction during late postnatal stages. It has been shown that spinal cord injuries are causally related to significant degenerative changes in bone properties. Nevertheless, information about a possible influence of the spinal cord on bone remodelling in adult healthy animals is missing. The aim of this research work was to assess possible morphological changes of the cervical vertebral canal of juvenile and aged rats during the ontogenetic period of adulthood that would justify the suggested influence. Since the spinal cord of rats increases its size with ageing, we analysed whether morphometric changes are occurring in the vertebral canal that would indicate bone remodelling in response to said growth. To this end, we used three complementary morphometric methods to describe the canal of the cervical and the first thoracic vertebrae. Geometric morphometric analyses evidence scarce variation in size and shape between juvenile and aged rats suggesting that, in general terms, the canal morphology of cervical vertebrae is already prepared in early adulthood to host the growing spinal cord. C3 was the only vertebra that showed consistent variation for the variables of canal thickness, perimeter, height and area. This regional variation may be linked to the patterns described for the changing spinal cord.